2018
DOI: 10.1155/2018/6109723
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture Treatment Alleviates the Remifentanil-Induced Hyperalgesia by Regulating the Activities of the Ventral Posterior Lateral Nucleus of the Thalamus Neurons in Rats

Abstract: Mechanisms underlying remifentanil- (RF-) induced hyperalgesia, a phenomenon that is generally named as opioid-induced hyperalgesia (OIH), still remain elusive. The ventral posterior lateral nucleus (VPL) of the thalamus, a key relay station for the transmission of nociceptive information to the cerebral cortex, is activated by RF infusion. Electroacupuncture (EA) is an effective method for the treatment of pain. This study aimed to explore the role of VPL in the development of OIH and the effect of EA treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 84 publications
0
7
0
Order By: Relevance
“…Acupuncture reduces pain by inhibiting this activation ( Lin et al, 2016 ; Wang J. Y. et al, 2018 ). (5) Acupuncture can regulate the entire brain area network of pain stimulation by adjusting the interaction between various brain functional areas and neurotransmitters, producing analgesic effects ( Yuan et al, 2018 ; Zhao et al, 2018 ). (6) Acupuncture exerts analgesic effects by mediating mitogen-activated protein kinase (MAPK) signaling pathways, including the spinal cord p38/MAPK ( Fang et al, 2013 ; Liang et al, 2016 ), extracellular-signal-regulated kinase ( Choi et al, 2012 ; Park et al, 2014 ), c-Jun N-terminal kinase ( Lee et al, 2013 ), and nuclear factor kappa-B pathways ( Park et al, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…Acupuncture reduces pain by inhibiting this activation ( Lin et al, 2016 ; Wang J. Y. et al, 2018 ). (5) Acupuncture can regulate the entire brain area network of pain stimulation by adjusting the interaction between various brain functional areas and neurotransmitters, producing analgesic effects ( Yuan et al, 2018 ; Zhao et al, 2018 ). (6) Acupuncture exerts analgesic effects by mediating mitogen-activated protein kinase (MAPK) signaling pathways, including the spinal cord p38/MAPK ( Fang et al, 2013 ; Liang et al, 2016 ), extracellular-signal-regulated kinase ( Choi et al, 2012 ; Park et al, 2014 ), c-Jun N-terminal kinase ( Lee et al, 2013 ), and nuclear factor kappa-B pathways ( Park et al, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, human brain imaging studies have shown that mean VPL volume is strongly associated with average and worst pain intensity, and abnormal connectivity between the VPL and other brain regions, such as the postcentral gyrus and insula, has been confirmed in patients suffering from pain [ 15 , 16 , 43 ]. In rodents, the spontaneous spike rate and the oscillation of local field potentials in the VPL have been reported to be increased in remifentanil-induced hyperalgesia [ 21 ]. In line with these findings, we further revealed an increase in VPL TC neuronal activity in the SNI-evoked neuropathic pain state.…”
Section: Discussionmentioning
confidence: 99%
“…Since an acupoint combination treatment efficacy is higher than a single acupoint [ 46 , 47 ], in clinical application, acupoints are used in conjunction with each other [ 48 ]. ZHANG X. et al reported that in patients with liver cancer, transcutaneous electrical stimulation of Neiguan (PC 6) and Jianshi (PC 5) improves gastrointestinal disturbances caused by transcatheter arterial chemoembolization [ 49 ].…”
Section: Discussionmentioning
confidence: 99%